Agritourism entrepreneurship in Greece: policy framework, inhibitory factors and a roadmap for further development - Panagiota Dionysopoulou (Goodwood Publishing, 2020)
Purpose: This paper aimed to examine how agritourism as a mild form of tourism can contribute to sustainable tourism development. Research methodology: A primary survey was conducted using a closed-type questionnaire of multiple-choice questions and sent to a respective enterprise sample. Results: The survey's output refers to the steps and measures that need to be taken for the further development of agritourism in Greece and its driving force as a pillar of sustainability growth. Limitations: The research addressed certain methodological issues, such as the difficulty of collecting the sample, since agritourism companies are not in total registered in Greece. There was also difficulty obtaining contact details (email, fax) from the list of final approved investments of the National Strategic Reference Framework. Contribution: The purpose is to present the views of agritourism entrepreneurs on their industry and identify the possible problems they encountered during their businesses' start-up and operation due to the legal or financial framework. Also, the state's role in this direction is examined and proposals are made for the further development of agritourism in Greece. Keywords: Farmer, Law 4276/2014, Legal framework of agritourism, National strategic reference framework, Rural tourism, State aid, Sustainable development